Lightweight mobile Ad Hoc network authentication scheme based on blockchain - Xu ZHANG; Xin MA (网络与信息安全学报)
In order to solve the problem that the existing authentication method can’t track the vulnerable of malicious nodes and depends on the centralized authentication center,based on the de-centralization,tamper-proof and traceable characteristics of blockchain technology,a distributed lightweight mobile Ad Hoc network authentication scheme was proposed.It included the establishment of peer-to-peer network,the design of certification ledger and the choice of consensus mechanism.Then the role of smart contracts was analyzed and discussed.In this scenario,when the maximum transmission delay τmax between a pair of peers is given,the relationship between node authentication timeδand network size <msubsup> N t <mtext>all</mtext> </msubsup>is satisfied with ( <msubsup> N t <mtext>all</mtext> </msubsup> 3 +7 ) τ <mtext>max</mtext> ≤δ≤3(<msubsup> N t <mtext>all</mtext> </msubsup> +1) τ <mtext>max</mtext> .